2011
DOI: 10.1088/0953-8984/23/11/115401
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic evaluation of the Jahn–Teller effect parameters. Application to ZnSe:Cr2 +

Abstract: A method is constructed that uses ultrasonic experiments to evaluate the parameters of the Jahn-Teller (JT) effect in impurity centers in crystals. The method is based on measurements of temperature dependent attenuation and phase velocity and does not require assumptions about mechanisms of relaxation. The results are illustrated by measurements performed on the impurity system ZnSe:Cr(2+), in which the Cr(2+) ion has a threefold degenerate T term in the ground state, subject to the [Formula: see text] JT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 18 publications
0
18
0
6
Order By: Relevance
“…Неоднородное по сечению увеличение затухания акустических волн до лазерного облучения в образцах можно также связать с неравномерным распределением ионов Fe 2+ по образцам. В этом случае значение α JT будет, согласно современным представле-ниям [14], связано с изменением упругих модулей C i j и временем релаксации τ между состояниями туннели-рующих через барьер электронов:…”
Section: таблица 2 относительное изменение упругих модулейunclassified
See 1 more Smart Citation
“…Неоднородное по сечению увеличение затухания акустических волн до лазерного облучения в образцах можно также связать с неравномерным распределением ионов Fe 2+ по образцам. В этом случае значение α JT будет, согласно современным представле-ниям [14], связано с изменением упругих модулей C i j и временем релаксации τ между состояниями туннели-рующих через барьер электронов:…”
Section: таблица 2 относительное изменение упругих модулейunclassified
“…Однако полученные в работе [13] методом синхротронной дифрактометрии значения фотодеформации ε ∼ 10 −4 не соответствуют величинам фотоиндуцированных полей (E ph ∼ 10 7 V/m), достигнутых с помощью облучения ксеноновой лампой образца НЛ, содержащего ионы железа. Это обстоятель-ство не позволяет объяснить полученные результаты только пьезоэффектом, хотя сам факт влияния примерно такой же концентрации ионов Fe 2+ , Cr 2+ , Ni 2+ , V 2+ на упругие характеристики полупроводниковых кристаллов типа ZnSe был обнаружен в работе [14]. Причем са-ми авторы объясняют полученные результаты именно присутствием ЯТ-эффекта в допирующих ионах.…”
Section: Introductionunclassified
“…Hence we can define these constants from the experimental data on ultrasonic attenuation using the method introduced in Refs. 5,6 . As it was shown in these papers, relaxation attenuation of the shear ultrasonic waves is given by the following expression:…”
Section: +mentioning
confidence: 99%
“…Along with traditional methods of investigation of electronic structure, dynamics and local symmetry of crystal dopants and other active centers in polyatomic systems by means of experimental electron spin resonance (ESR) and pulse techniques using electron spin echo (ESE, ES-EEM spectroscopy) [1][2][3][4] , recent studies of II-VI:3d and III-V:3d crystals by means of ultrasonic experiments demonstrated the efficiency of this novel approach in obtaining important information about the structure and properties of Jahn-Teller effect (JTE) centers in such crystals [5][6][7][8] . Ultrasonic experiments are uniquely suited for investigation of JTE problems because the interaction of the ultrasound wave of strain produces characteristic anomalies in speed, relaxation, and attenuation when its direction of propagation and polarization coincides with the direction of JTE distortions.…”
Section: Introductionmentioning
confidence: 99%
“…But in view of possible application in quantum computing, magneto‐acoustic investigation is deemed to be important. We have performed such experiments in wurtzite CdSe:Cr 2+ , fluorite SrF 2 :Cr 2+ , and sphalerite ZnSe:Cr 2+ single crystals. All of these materials manifest the JTE but only ZnSe:Cr 2+ exhibits magnetic field dependence of the acoustic properties.…”
Section: Introductionmentioning
confidence: 99%